The role of CXCL10 as a biomarker for immunological response among patients with leprosy: a systematic literature review - Prakoeswa,Flora Ramona Sigit; Haningtyas,Nabila; Dewi,Listiana Masyita; Handoko,Ellen Josephine; Azenta,Moch. Tabriz; Ilyas,Muhana Fawwazy (PeerJ, 2024)
Introduction Involvement of a chemokine known as C-X-C motif chemokine ligand 10 or CXCL10 in the immunopathology of leprosy has emerged as a possible immunological marker for leprosy diagnosis and needed to be investigate further. The purpose of this systematic review is to assess CXCL10’s potential utility as a leprosy diagnostic tool and evaluation of therapy. Methods This systematic review is based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020. A thorough search was carried out to find relevant studies only in English and limited in humans published up until September 2023 using PubMed, Scopus, Science Direct, and Wiley Online Library database with keywords based on medical subject headings (MeSH) and no exclusion criteria. The Newcastle-Ottawa Scale (NOS) was utilized for quality assessment, while the Risk of Bias Assessment tool for Non-randomized Studies (RoBANS) was utilized for assessing the risk of bias. Additionally, a narrative synthesis was conducted to provide a comprehensive review of the results. Results We collected a total of 115 studies using defined keywords and 82 studies were eliminated after titles and abstracts were screened. We assessed the eligibility of the remaining 26 reports in full text and excluded four studies due to inappropriate study design and two studies with incomplete outcome data. There were twenty included studies in total with total of 2.525 samples. The included studies received NOS quality evaluation scores ranging from 6 to 8. The majority of items in the risk bias assessment, using RoBANS, across all included studies yielded low scores. However, certain items related to the selection of participants and confounding variables showed variations. Most of studies indicate that CXCL10 may be a helpful immunological marker for leprosy diagnosis, particularly in leprosy reactions as stated in seven studies. The results are better when paired with other immunological markers. Its effectiveness in field-friendly diagnostic tools makes it one of the potential biomarkers used in diagnosing leprosy patients. Additionally, CXCL10 may be utilized to assess the efficacy of multidrug therapy (MDT) in leprosy patients as stated in three studies. Conclusion The results presented in this systematic review supports the importance of CXCL10 in leprosy diagnosis, particularly in leprosy responses and in tracking the efficacy of MDT therapy. Using CXCL10 in clinical settings might help with leprosy early diagnosis. Yet the findings are heterogenous, thus more investigation is required to determine the roles of CXCL10 in leprosy while taking into account for additional confounding variables.
Keywords: CXCL10; Leprosy; Immunological marker; Diagnosis; Systematic review